2008
DOI: 10.1051/agro:2007062
|View full text |Cite
|
Sign up to set email alerts
|

Soil-erosion and runoff prevention by plant covers. A review

Abstract: Soil erosion is a critical environmental problem throughout the world's terrestrial ecosystems. Erosion inflicts multiple, serious damages in managed ecosystems such as crops, pastures, or forests as well as in natural ecosystems. In particular, erosion reduces the waterholding capacity because of rapid water runoff, and reduces soil organic matter. As a result, nutrients and valuable soil biota are transported. At the same time, species diversity of plants, animals, and microbes is significantly reduced. One … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
178
2
6

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 571 publications
(191 citation statements)
references
References 152 publications
(147 reference statements)
5
178
2
6
Order By: Relevance
“…They improve the stability of soil aggregates (Goulet et al, 2004) and protect them from the impacts of rain drops, reducing aggregate breakdown and soil detachment (Dabney et al, 2001). Service crops also prevent soil crusting and sealing (Durán Zuazo and Rodríguez Pleguezuelo, 2008). As an example, a 4-year experiment measuring water erosion in Gerlach troughs under various treatments (tillage, Secale cereale and Brachypodium distachyon service crops) showed soil loss reductions by 91% and 93% with Secale and Brachypodium, respectively (Ruiz-Colmenero et al, 2013).…”
Section: Services and Disservices Of Service Crops In Vineyardsmentioning
confidence: 99%
“…They improve the stability of soil aggregates (Goulet et al, 2004) and protect them from the impacts of rain drops, reducing aggregate breakdown and soil detachment (Dabney et al, 2001). Service crops also prevent soil crusting and sealing (Durán Zuazo and Rodríguez Pleguezuelo, 2008). As an example, a 4-year experiment measuring water erosion in Gerlach troughs under various treatments (tillage, Secale cereale and Brachypodium distachyon service crops) showed soil loss reductions by 91% and 93% with Secale and Brachypodium, respectively (Ruiz-Colmenero et al, 2013).…”
Section: Services and Disservices Of Service Crops In Vineyardsmentioning
confidence: 99%
“…In regard to the tree soil protection effect, Durán and Rodríguez (2008) indicated that it depends on the percentage of the soil coverage, the modification caused by the foliage in the distribution pattern of drops falling on the soil surface, and the soil coverage by leaf litter under the trees. Experiments made in olive trees in Southern Spain have shown decreased erosion after the fruit trees were grown; however, that reduction is lower when soil is bare without leaf litter under the trees (Gómez et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…L'utilisation excessive d'herbicides en agriculture conduit en outre à l'apparition de phéno-mènes d'érosion et de lessivage des sols [2,3]. Les vergers pentus y sont donc particulièrement sensibles.…”
Section: Introductionunclassified